The role of scaffolding in students' geometry analogical reasoning from gender - Hodiyanto Hodiyanto; Dwi Juniati (IKIP PGRI Pontianak, 2022)
The purpose of this study is to find out: (1) the process of reasoning analogy of students in geometry before being given scaffolding in terms of gender and (2) the process of reasoning analogy of students in geometry after being given scaffolding in terms of gender. The research method used in this research is a case study. This research was conducted on students who have taken basic geometry and analytic geometry courses, 4th semester students of the Mathematic Education Study Program, IKIP PGRI Pontianak. The subjects taken in this study amounted to two people (male and female) and had moderate ability. The data collection tools used were tests and interviews (to determine the analogy reasoning process of students). Before students are given scaffolding, students are first given an analogy reasoning test then followed by interviews and scaffolding. Data analysis techniques used in this research are data reduction, display and conclusion. Based on the results of the research and discussion, it can be concluded that (1) the analogy reasoning of male students before being given scaffolding almost entered the mapping meaning that the mapping stage of students was still lacking while the analogy reasoning of female students was only at the inferring, (2) after being given scaffolding, both male and female students have gone through four stages of the analogy reasoning process from the encoding, inferring, mapping stage applying Thus, the existence of scaffolding has an influence on students' analogical reasoning.